Serotonin Activates Bacterial Quorum Sensing and Enhances the Virulence of Pseudomonas aeruginosa in the Host - Knecht, Leslie D.; O'Connor, Gregory; Mittal, Rahul; Liu, Xue Z.; Daftarian, Pirouz; Deo, Sapna K.; Daunert, Sylvia (EBioMedicine, 2016)
Bacteria in humans play an important role in health and disease. Considerable emphasis has been placed in understanding the role of bacteria in host-microbiome interkingdom communication. Here we show that serotonin, responsible for mood in the brain and motility in the gut, can also act as a bacterial signaling molecule for pathogenic bacteria. Specifically, we found that serotonin acts as an interkingdom signaling molecule via quorum sensing and that it stimulates the production of bacterial virulence factors and increases biofilm formation in vitro and in vivo in a novel mouse infection model. This discovery points out at roles of serotonin both in bacteria and humans, and at phenotypic implications not only manifested in mood behavior but also in infection processes in the host. Thus, regulating serotonin concentrations in the gut may provide with paradigm shifting therapeutic approaches. •Serotonin can act as a bacterial quorum sensing molecule through the LasR quorum sensing pathway.•Serotonin stimulates quorum sensing-dependent virulence factor and biofilm production in Pseudomonas aeruginosa.•Serotonin exacerbates Pseudomonas aeruginosa infection in vivo. Bacteria play many roles in human health and disease, thus investigating host-microbiome communication is of great importance. To this end, our research demonstrates that serotonin, a neurotransmitter responsible for mood in the brain and motility in the gut, can act as a bacterial communication molecule for pathogenic bacteria, specifically Pseudomonas aeruginosa. Serotonin increases Pseudomonas virulence factor and biofilm production in vitro and enhances virulence in infected mice. These findings are beneficial in understanding the impact of the microbiome on human health and may open the door for novel treatments for human disease.